Interrelation of Religion and Culture in Gunungan Tradition Cosmology: Islamic and Javanese Perspectives - Ubaidillah, Ubaidillah; Marpuah, Siti (Universitas Islam Negeri Madura, 2021)
Philosophically, the science of The Qur’an about mountains is interpreted as a system of local awareness in the form of spiritual communication in the gunungan tradition of Javanese society. The concept of mountains in the Qur’an is scientific proof (kauniyah) of the Oneness of God as the Javanese interpret it as the concept of Gusti Manunggal. This dialectical relationship can be traced through the meaning of mountain cosmology in the Qur’an and Javanese philosophy in the perspective of interrelation between religion and culture. This study aims to explain mountains in the scientific perspective of the Qur’an with various functions which philosophically have a strong relationship in the gunungan tradition of the Garabek, Tumpeng, Slametan, and Sekaten rituals as the embodiment of tauhid in Central Java or Panjang-jimat in West Java. The method used is a thematic interpretation study with a descriptive narrative approach. Research on mountain cosmology or gunungan in the perspective of Islam and Javanese culture finds that (1) Gunungan is a form of symbolic communication that functions as an adhesive for the ordinary people on the one hand and at the same time spiritual. (2) The mountain is a universal system that affects the life of the Javanese people in fulfilling their life needs in an ecosystem function. (3) The gunungan tradition is a medium for praying, gratitude as a form of application, safety, and peace, as well as a medium for the spread of Islam. It can be concluded that the relationship between Islam and Javanese culture is a unified and unique Islamic characteristic in expressing theological and ecological awareness.